2009
DOI: 10.1098/rspb.2009.1011
|View full text |Cite
|
Sign up to set email alerts
|

Shifting latitudinal clines in avian body size correlate with global warming in Australian passerines

Abstract: Intraspecific latitudinal clines in the body size of terrestrial vertebrates, where members of the same species are larger at higher latitudes, are widely interpreted as evidence for natural selection and adaptation to local climate. These clines are predicted to shift in response to climate change. We used museum specimens to measure changes in the body size of eight passerine bird species from south-eastern Australia over approximately the last 100 years. Four species showed significant decreases in body siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 48 publications
5
94
4
1
Order By: Relevance
“…While warming generally reduces body size within local communities [50,54,55], it is not clear whether large body-sized species tend to shift or expand their ranges more easily than smaller ones [24]. It is worth noting that species at higher trophic positions were homogeneously distributed across elevations; so range expansions in these groups would not occur.…”
Section: Discussionmentioning
confidence: 99%
“…While warming generally reduces body size within local communities [50,54,55], it is not clear whether large body-sized species tend to shift or expand their ranges more easily than smaller ones [24]. It is worth noting that species at higher trophic positions were homogeneously distributed across elevations; so range expansions in these groups would not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Starting at the population level, two recent reviews have shown heterogeneity in both the magnitude and the direction of size responses to warming [12,13]. The degree to which organism size is affected by temperature varies across taxa, but some general patterns can be recognized.…”
Section: Closed Communitiesmentioning
confidence: 99%
“…This trend has also been reported in a number of sedentary and migratory bird species, such as House Sparrows (Passer domesticus; Johnston and Selander 1973), Crested Duck (Lophonetta specularioides; Bulgarella et al 2007), Torrent Duck (Merganetta armata; GutiĂ©rrez-Pinto et al 2014) and some Andean passerine birds (Blackburn and Ruggiero 2001), but not in the Rufous-necked Snowfinch (Montifringilla ruficollis; Lu et al 2009). From a thermoregulatory viewpoint, increased body mass could be an adaptation to colder temperatures (Gardner et al 2009;Teplitsky and Millien 2014); the reduced surface area to volume ratio of larger-bodied individuals means that they lose proportionately less heat than smaller-bodied birds (Mayr 1956(Mayr , 1963Blackburn et al 1999).…”
Section: Geographic and Climatic Variation In Body Mass And Wing Lengthmentioning
confidence: 99%
“…Previous studies have demonstrated a positive relationship between body size and latitude in both birds and mammals (Ashton 2002a;Meiri and Dayan 2003;Gardner et al 2009;Olson et al 2009). However, limited information is available on altitudinal variation in body size (Hamilton 1961;Blackburn and Ruggiero 2001;Chown and Klok 2003;Wilson et al 2010;GutiĂ©rrez-Pinto et al 2014).…”
Section: Introductionmentioning
confidence: 99%